Effects of Core Stability Exercise and Neurosensorimotor Reflex Integration on the Crawling Ability of Children with Quadriplegi Spastic Cerebral Palsy: Case Report - Selma Safiannisa Haqia; Wahyu Tri Sudaryanto; Intan Herlinawati; Farid Rahman (Urecol Journal. Part D: Applied Sciences, 2022)
In children with cerebral palsy, core stability exercise is an important aspect that must be done as a basis and preparation for crawling. In addition, neurosensorimotor reflex integration is given to help control emotions so that children can cooperate when given exercise. These two methods are given because they can support the motor, sensory, and cognitive aspects of children. It is hoped that research outcomes can be achieved. To determine the effect of core stability exercise and neurosensorimotor reflex integration on the crawling ability on children with spastic quadriplegia cerebral palsy. Single subject research conducted on a 20-month-old spastic quadriplegious cerebral palsy child. Subjects were given core stability exercise and neurosensorimotor reflex integration for 4 weeks, therapy was carried out twice a week and follow-up measurements were made on children's motor development for 1 month. Evaluation of children's motoric measurement, using the GMFCS (Gross Motor Function Classification System) instrument. The baseline found that there was no significant development in the child's ability to crawl. However, at the second follow-up, the child was able to perform crawling movements even though the pattern was less than perfect. Creep becomes the basis for crawling. There was no significant improvement in children's motoric development, namely crawling after being given core stability exercise and neurosensorimotor reflex integration for one month.